Tools for wetland management: lessons learnt from a comparative assessment - Cools, J.; Johnston, Robyn M.; Hattermann, F.F.; Douven, W.; Zsuffa, I. (Elsevier, 2013)
This paper provides the synthesis of the special issue on the ''role of wetlands in river basin management'' and reviews lessons learnt from a comparative assessment of the presented case studies in Europe, Africa and Latin-America. Although wetlands are important for local communities and biodiversity, the services and products they deliver for local livelihoods and river basins are insufficiently known, and inadequately valued and understood by authorities. Wetlands are too often perceived as standalone elements and poorly integrated into river basin management plans. In this volume, an analytical framework is developed to formulate and compare wetland management options, also in data-poor contexts and to bridge the gap between science and policy. The framework is a set of tools and processes to structure the information flows needed to identify and score management options in terms of their impact, feasibility, vulnerability to future changes and trade-offs. In practice, it was found that the framework provided a useful set of tools to promote understanding and underpin negotiations. The major barrier for a better integration of wetlands in river basin management was found to be the lack of understanding of what the important issues were and the institutional capacity to organise cooperation and consequent implementation of the agreed plans. This paper presents the following conclusions. Firstly, rapid assessment tools and simplified scoring methods were used and proved useful in explaining issues across sectors and scales, and were important in creating mutual understanding, even though they did not necessarily present new insights for local or disciplinary experts. Secondly, in order to improve the knowledge base, an integrated database is developed, especially with regard to water quantity simulation at the river basin scale and wetland scale, potential habitat availability and the quantification of adaptive and institutional capacity, including the impact of future changes. Data has been compiled from various, scattered sources, including global data sets, sectoral wetland and/or river basin-specific quantitative and qualitative data sets. Thirdly, in case of limited data availability, rather than improving the accuracy of available quantitative data, it is proposed to better use alternative qualitative sources of data, from local experts, authority representatives and wetland users.